How much schizophrenia do famines cause? - Cormac Ó Gráda; Chihua Li; L. H. Lumey (University College Dublin, UCD School of Economics, 2023)
Since the 1970s, famines have been widely invoked as natural experiments in research into the long-term impact of foetal exposure to nutritional shocks. That research has produced compelling evidence for a robust link between foetal exposure and the odds of developing schizophrenia. However, the implications of that research for the human cost of famines in the longer run has not been investigated. We address the connection between foetal origins and schizophrenia with that question in mind. The impact turns out to be very modest - much less than one per cent of the associated famine death tolls - across a selection of case studies.
Keywords: I1; N10; Q54; 330; famine; schizophrenia; foetal origins